THE INNOVATION OF THE LATE BALLETS BY SERGEI PROKOFIEV (Mūzikas akadēmijas raksti, 2024)
The creative life of Sergei Prokofiev has always been linked with ballet. His first contribution to the above genre, namely, music for the ballet The Chout, was written as early as in 1915, whereas the last (The Tale of the Stone Flower) – in 1950 towards the decline of his life. This timeline quite symbolically highlights the essential place of the genre in question within the context of Prokofiev’s creative effort. Owing to such a formal criterion as timeline, his ballets can relatively be divided into two distinct groups, referred to as early and late. However, the difference between these groups is marked not only (and not primarily) by the chronological factor alone, but also by such factors as the interpretation of the genre, aesthetics, implementation of the author’s concept in music, including also the addressee, who has set very tangible tasks for the composer to solve. As to the latter, Prokofiev has always been noted for his very exact approach.